Coelomata and Not Ecdysozoa: Evidence From Genome-Wide Phylogenetic Analysis - Wolf, Yuri I.; Rogozin, Igor B.; Koonin, Eugene V.

(untitled) (Genome Research, 2004)
Relative positions of nematodes, arthropods, and chordates in animal phylogeny remain uncertain. The traditional tree topology joins arthropods with chordates in a coelomate clade, whereas nematodes, which lack a coelome, occupy a basal position. However, the current leading hypothesis, based on phylogenetic trees for 18S ribosomal RNA and several proteins, joins nematodes with arthropods in a clade of molting animals, Ecdysozoa. We performed a phylogenetic analysis of over 500 sets of orthologous proteins, which are represented in plants, animals, and fungi, using maximum likelihood, maximum parsimony, and distance methods. Additionally, to increase the statistical power of topology tests, the same methods were applied to concatenated alignments of subunits of eight conserved macromolecular complexes. The majority of the methods, when applied to most of the orthologous clusters, both concatenated and individual, grouped the fly with humans to the exclusion of the nematode, in support of the coelomate phylogeny. Trees were also constructed using information on insertions and deletions in orthologous proteins, combinations of domains in multidomain proteins, and presence-absence of species in clusters of orthologs. All of these approaches supported the coelomate clade and showed concordance between evolution of protein sequences and higher-level evolutionary events, such as domain fusion or gene loss.